Pengembangan Aplikasi Mobile Manajemen Keuangan Dengan Metode Scrum (Studi Kasus Mahasiswa FILKOM UB) - Januari Arka; Adam Hendra Brata; Komang Candra Brata (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
FM App is a financial management application to solve financial problems for students of the Faculty of Computer Science Brawijaya University (FILKOM UB). FM App can be used anywhere and anytime because it is developed with an Android mobile platform which is mostly a type of smartphone used by students and Firebase to store data in real time. FM application has several features to solve financial problems of FILKOM UB students, such as daily expenses that exceed daily limits, expenditures that have been used cannot be tracked, unexpected expenses, and purchase planning. FM App uses the Naive Bayes algorithm to recommend students' financial status when unexpected expenses are made. In addition, this development requires a method that has a direct approach to users, requires continuous feedback, increases developer productivity, and accelerates system development. Therefore, the Scrum method has been used. The FM application has a 100% recommendation accuracy value, so it can be concluded that the application can recommend financial status with 100% correct after unexpected expenses are made. Besides that, FM App has a value of 79 on usability, so it can be categorized that the application has a good level of ease of use.